Dual Laser Study of Non‐Degenerate Two Wavelength Upconversion Demonstrated in Sensitizer‐Free NaYF4:Pr Nanoparticles. Issue 7 (1st February 2021) - de Prinse, Thomas J.; Karami, Afshin; Moffatt, Jillian E.; Payten, Thomas B.; Tsiminis, Georgios; Teixeira, Lewis Da Silva; Bi, Jingxiu; Kee, Tak W.; Klantsataya, Elizaveta; Sumby, Christopher J.; Spooner, Nigel A.
Abstract: Understanding the upconversion pathways of a rare‐earth dopant is crucial to furthering the use of that material, either toward applications in imaging or elsewhere. This work outlines a new analysis approach that consists of using two synchronized widely‐tunable laser sources to explore the properties of upconverting materials. By examining sensitizer‐free rare‐earth nanoparticles based on a matrix of hexagonal sodium yttrium tetrafluoride (β‐NaYF4 ) doped with praseodymium but no ytterbium sensitizer, a "non‐degenerate" two‐color upconversion fluorescence at a combined excitation of 1020–850 nm is shown. This insight demonstrates the ability of this technique to locate and interrogate novel upconversion pathways. The dopant level of the nanoparticles could be modified without altering other factors, such as the particle's shape or size, that would also change optical properties and this allows investigation of the dopant‐level dependency of the optical properties. The approach also allows exploration of the time delay domain between the arrival times of the two non‐degenerate excitation pulses, which allows modulation of the brightness from the visible light emissions. This work opens up the parameter space for the systematic synthesis and characterization of new materials with non‐degenerate upconversion emission. Abstract : A dual tunable laser system is assembled that is capable of scanning continuously over the visible and near‐infrared. Dual excitation of materials allows for the detection of "non‐degenerate" upconversion, in which two colors excite a pathway that cannot be observed with a single excitation source. To demonstrate this system, NaYF4 :Pr 3+ nanoparticles are synthesized and characterized. These materials show a strong non‐degenerate upconversion transition in the near‐infrared.